2006
DOI: 10.1038/sj.ijo.0803207
|View full text |Cite
|
Sign up to set email alerts
|

The criterion validity of a last 7-day physical activity questionnaire (SAPAQ) for use in adolescents with a wide variation in body fat: the Stockholm Weight Development Study

Abstract: Objective: The aim of the present study was to assess the criterion validity of a newly developed self-reported last 7-day physical activity questionnaire (SAPAQ) for use in Swedish adolescents with a wide variation in body fatness. Measurements: We compared the self-reported total number of MET-minutes with objectively assessed variables of physical activity obtained by accelerometry in 49 (18 male, 31 female subjects) 17-year-old adolescents. Results: Self-reported physical activity was significantly and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
(10 reference statements)
1
19
0
3
Order By: Relevance
“…A análise da reprodutibilidade foi efetuada em 50 instrumentos e da validade em 71. Ou seja, em alguns instrumentos foi analisada apenas a reprodutibilidade (n = 8) 36,37,38,39,40,41,42,43 , em outros a validade (n = 29) 16,18,21,25,28,30,31,32,33,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A análise da reprodutibilidade foi efetuada em 50 instrumentos e da validade em 71. Ou seja, em alguns instrumentos foi analisada apenas a reprodutibilidade (n = 8) 36,37,38,39,40,41,42,43 , em outros a validade (n = 29) 16,18,21,25,28,30,31,32,33,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60 .…”
Section: Resultsunclassified
“…A maioria destes instrumentos (33/52) 19,20,21,22,23,24,25,27,28,32,35,38,40,41,46,47,50,51,53,55,56,57,61,64,68,69,70,71,72,73,74 não permitia realizar estimativas do nível de atividade física dos adolescentes de acordo com as recomendações dos 300 min/semana 75 . Dos que realizavam tais estimativas, tirando uma entrevista (7-Day Physical Activity Recall) 16,24,60 , todos eram questionários (n = 18) 17,20,29,34,42,43,45,48,61,67,76,77,78,79,80,…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In older children (6–11 years), similar correlations were reported for the PA Questionnaire for Parents and Teachers21 and the ACTIVITY Questionnaire 22. In adolescents (12–18 years), correlation coefficients were somewhat higher for the previous day physical activity recall (PDPAR) (r=0.7723) and the Swedish Adolescent Physical Activity Questionnaire (SAPAQ) (r=0.5124). …”
Section: Self-report Methods For Assessing Pamentioning
confidence: 99%
“…This questionnaire has a short version (seven questions) and long version (27 questions) that evaluate the frequency and duration of activities performed in the last seven days within four different domains of PA (leisure-time, transportation, household activities, and occupational) (Craig et al, 2003). Although the IPAQ can reasonably estimate leisure-time physical activity (LTPA) and the time spent in community activities, studies have shown that the IPAQ overestimates PA in the other two PA domains including, household activities and physical labor (Ekelund, Neovius, Linne, & Rossner, 2006;Hallal et al, 2010;Johnson-Kozlow, Sallis, Gilpin, Rock, & Pierce, 2006;Ramírez-Marrero, Rivera-Brown, Nazario, Rodríguez-Orengo, Smit, & Smith, 2008;Sebastião et al, 2012). Further, the IPAQ is unable to identify factors that enable people to change their behavior.…”
Section: Introductionmentioning
confidence: 99%